The appearance and development of neurotransmitter sensitivity in Xenopus embryonic spinal neurones in vitro. - Bixby, J L (1984)
We have determined the time of onset and examined some of the properties of neurotransmitter sensitivity in Xenopus spinal neurones developing in dissociated cell culture. These cells are initially insensitive, but acquire responses to several agonists over a period of 6 h. Nearly one-third of the neurones were depolarized by gamma-aminobutyric acid (GABA) or by both GABA and glycine; these cells were not affected by glutamate. The reversal potential of the ionophoretic GABA response is -35 mV. These neurones are likely to be Rohon-Beard neurones. Roughly two-thirds of the neurones were depolarized by glutamate and hyperpolarized by GABA and by glycine. The reversal potential of the ionophoretic GABA response is -58 mV. These neurones are likely to include motoneurones. A quantitative measure of the sensitivity to a given GABA dose was obtained at early and intermediate stages of development. The mean 'sensitivity index' (ionophoretic sensitivity/input resistance) for both classes of neurones in vitro was initially the same as that seen in Rohon-Beard neurones in vivo. This sensitivity index did not increase with time in culture to attain the value at intermediate stages in vivo. The development of chemosensitivity in Rohon-Beard-like neurones in these cultures resembles that of Rohon-Beard neurones in the spinal cord with respect to the time of onset of responses to GABA, the reversal potential, pharmacology and desensitization of these responses, and the spectrum of agonists to which they are sensitive. It differs in the absence of a developmental increase in sensitivity to GABA. The development of chemosensitivity in motoneurone-like neurones in these cultures parallels that of Rohon-Beard-like neurones, with respect to the time of onset and level of sensitivity, as well as susceptibility to pharmacological blockers. Several features of normal neurotransmitter sensitivity, like features of the action potential, differentiate in culture in the absence of normal cellular interactions.